Partisipasi Masyarakat Dalam Pembentukan Undang-Undang Cipta Kerja - Saiya, Aprillia Jultje; Alfons, Saartje Sarah; Tita, Heillen Martha Yosephine (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The formation of good and correct regulations is based on the principle of the formation of statutory regulations. In the formation of the Job Creation Law, the procedure that was followed later became a polemic when this Law did not involve procedural community participation.Purposes of the Research: This writing aims to identify and examine the legal consequences of the establishment of the Job Creation Act.Methods of the Research: The method used in conducting a study of this problem is normative juridical with a legal and conceptual approach.Results of the Research: The legal consequence of the establishment of the Job Creation Act is the emergence of disinformation in the community regarding the contents of the Job Creation Act, so many parties have asked the Constitutional Court to conduct a judicial review or judicial review of the Job Creation Act. This is because the creation of the Copyright Act did not pay attention to the principles of openness and public participation in the process of its formation. Community Social Institutions (LSM) and the Confederation of Indonesian Trade Unions (KSPI) when asking for the draft of the Job Creation Bill, the government could not show that the people who were the target of the regulation should have easy access to the draft law. And also KSPI admitted that it was not involved in the formation of the Job Creation Act